Assessment of Enterococcus durans F21 Isolated from Lben, a Moroccan Fermented Milk as a Biopreservative Agent - Benkirane, Ghita; Gharsallaoui, Adem; Manni, Laila; Chihib, Nour-Eddine; Dumas, Emilie; Ananou, Samir (Applied Food Biotechnology, 2023)
Abstract Background and Objective: Lactic acid bacteria used in food processing for a long time are known for their benefits to consumers and their ability to produce natural antimicrobial compounds used as bio-preservatives in foods. The aim of the present study was the characterization and assessment of F21 strain, isolated from Lben (a traditional Moroccan fermented milk), as food biopreservative. Material and Methods: Isolate F21 was isolated from Lben, subjected to screening of inhibitory activity production, and identified based on morphological, biochemical and molecular identification. Then, the production and physicochemical characterization of the antagonistic substance were determined. Also, the safety profiling and biotechnological properties of isolate were evaluated. Finally, a biopreservative powder with antimicrobial activity was produced and assessed in various food systems (milk, ground beef and fresh cheese). Results and Conclusion: Of the isolated lactic acid bacteria, Enterococcus durans F21, isolated from Lben (a traditional Moroccan fermented milk), was remarkably endowed with interesting enterocin-like substance (heat stable and pH resistant) active against potentially pathogens and food spoilages (Listeria monocytogenes, Listeria innocua, Enterococcus faecalis, Brochothrix thermosphacta, and Mycobacterium smegmatis). Concerning the safety properties, Enterococcus durans F21 was not hemolytic, sensible to antibiotics tested, unable to produce biogenic amines and other virulence enzymes (gelatinase, DNase and urease). In addition, Enterococcus durans F21 showed satisfactory biotechnological characteristics such as acidification power, exopoly-saccharides production and antioxidant activity. The biopreservative powder containing enterocin-like substance F21 that was achieved via freeze-drying showed a minimum inhibition concentration of 60 AU ml-1 against Listeria monocytogenes in culture media. In addition, this biopreservative powder (at 665 AU ml-1) was able to improve safety and shelf-life of numerous foods (milk, Jben and ground beef). Thus, these results provided foundations for further uses of Enterococcus durans F21 as producer of potential food biopreservative agent. Conflict of interest: The authors declare no conflict of interest.